PENYULUHAN PENTINGNYA MENINGKATKAN PENGETAHUAN DALAM MENJAGA KESEHATAN REPRODUKSI PADA REMAJA DI MAN 6 ACEH BESAR - Yarah, Saufa; Muharrina, Cut Rahmi; Amalia, Shinta; Lysabena (Yayasan Sagita Akademia Maju, 2024)
Adolescent reproductive health is defined as the healthy condition of the systems, functions and processes of the reproductive organs of adolescents, namely men and women aged 10-19 years and who are not yet married. Lack of knowledge about reproductive health will of course have an impact on attitudes that don't care about reproductive health. especially related to reproductive health. Adolescents, both male and female, experience various problems related to reproductive health such as unwanted pregnancies (KTD), sexually transmitted diseases (STDs) including Human Immunodeficiency Virus (HIV) infection, this is due, in part, to a lack of knowledge and caring attitude towards health. reproduction. This community service activity intervention aims to provide counseling about reproductive health to adolescents and then evaluate their level of knowledge before and after the counseling is carried out. The stages involve delivering the material using the lecture method, then a question and answer session and finally with a post-test by the participants. The results of the post-test conducted showed that counseling about reproductive health was effective in increasing the level of knowledge in adolescents. It is hoped that the impact of this activity will increase knowledge among teenagers and increase their caring attitude in maintaining their reproductive health.